Conditioned Medium of Bone Marrow Mesenchymal Stem Cells Involved in Acute Lung Injury by Regulating Epithelial Sodium Channels via miR-34c - Zhou, Zhiyu; Hua, Yu; Ding, Yan; Hou, Yapeng; Yu, Tong; Cui, Yong; Nie, Hongguang (Frontiers in Bioengineering and Biotechnology, 2021)
Background: One of the characteristics of acute lung injury (ALI) is severe pulmonary edema, which is closely related to alveolar fluid clearance. Mesenchymal stem cells (MSCs) secrete a wide range of cytokines, growth factors and miRNAs through paracrine action to participate in the mechanism of pulmonary inflammatory response, which increase the clearance of edema fluid, and promote the repair process of ALI. Epithelial sodium channel (ENaC) is the rate-limiting step in the sodium-water transport and edema clearance in the alveolar cavity, the role of bone marrow derived MSCs-conditioned medium (BMSCs-CM) in edema clearance and how miRNAs affect ENaC are still seldom known. Methods: CCK-8 cell proliferation assay was used to detect the effect of BMSCs-CM on the survival of AT2 cells. Real-time PCR (RT-PCR) and western blot were used to detect the expression of ENaC in AT2 cells. The effects of miR-34c on lung fluid absorption were observed in LPS-treated mice in vivo and the transepithelial short-circuit currents in the monolayer of H441 cells were examined by the Ussing chamber setup. Dual luciferase reporter gene assay was used to detect the target gene of miR-34c. Results: BMSCs-CM could increase the viability of mouse AT2 cells. RT-PCR and western blot results showed that BMSCs-CM significantly increased the expression of γ-ENaC subunit in mouse AT2 cells. MiR-34c could restore alveolar fluid clearance and lung wet/dry weight ratio in ALI animal model, and Ussing chamber assay revealed that miR-34c enhanced the amiloride-sensitive currents associated with ENaC activity in intact H441 cell monolayers. In addition, we observed higher expression of miR-34c in mouse AT2 cells administrated with BMSCs-CM, and the overexpression or inhibition of miR-34c could regulate the expression of ENaC protein and alter the function of ENaC. Finally, we detected MARCKS may be one of the target gene of miR-34c. Conclusions: Our results indicate that BMSCs-CM may alleviate LPS-induced ALI through miR-34c targeting MARCKS and regulate ENaC indirectly, which further explores the benefit of paracrine effects of BMSCs on edematous ALI.